Sanitation of House and School, Personal Hygiene and Infection of Soil Transmitted Helminths among Elementary School Students - Dina Merisa Damanik; Soeyoko Soeyoko; Adi Heru Sutomo (Intelektual Pustaka Media Utama, 2014)
In Indonesia, soil transmitted helminths (STH) infection is still a public health problem particularly in the child of elementary school age. The high of that infection was also supported by low environmental sanitation and poor personal hygiene. STH infection is one of 10 great of frequent diseases in Palue Island and in this region still able can be found an adult worm in feces even from regurgitate. This was observational analytic study by cross sectional design. The location of the study was Palue Island, Sikka Regency, East Nusa Tenggara. The repondents of the study was 100 students of eight elementary school. Diagnosis of STH infection was establised based on worm eggs examination in feces used floatation method. Questionnaire, and check list were the instruments for collecting data in this study. There were significant relationship between house’s environmental sanitation (p=0.043), school’s environmental sanitation (p= 0.000), personal hygiene (p = 0.032) with STH infection among the students of elementary school in Palue Island, Sikka Regency, East Nusa Tenggara. Multivariate analysis obtained that personal hygiene was the most influence variable to the STH infection in this region.